Conformational thermodynamics of biomolecular complexes: The histogram-based method. (August 2015) - Das, Amit; Sikdar, Samapan; Ghosh, Mahua; Chakrabarti, J
Abstract: Conformational changes in biomacromolecules govern majority of biological processes. Complete characterization of conformational contributions to thermodynamics of complexation of biomacromolecules has been challenging. Although, advances in NMR relaxation experiments and several computational studies have revealed important aspects of conformational entropy changes, efficient and large-scale estimations still remain an intriguing facet. Recent histogram-based method (HBM) offers a simple yet rigorous route to estimate both conformational entropy and free energy changes from same set of histograms in an efficient manner. The HBM utilizes the power of histograms which can be generated as accurately as desired from an arbitrarily large sample space from atomistic simulation trajectories. Here we discuss some recent applications of the HBM, using dihedral angles of amino acid residues as conformational variables, which provide good measure of conformational thermodynamics of several protein-peptide complexes, obtained from NMR, metal-ion binding to an important metalloprotein, interfacial changes in protein-protein complex and insight to protein function, coupled with conformational changes. We conclude the paper with a few future directions worth pursuing.